Prognostic Value of BRAF and KRAS Mutation in Relation to Colorectal Cancer Survival in Iranian Patients: Correlated to Microsatellite Instability - Nazemalhosseini-Mojarad, Ehsan; Kishani Farahani, Roya; Mehrizi, Maryam; Baghaei, Kaveh; Yaghoob Taleghani, Mohammad; Golmohammadi, Mina; Peyravian, Noshad; Ashtari, Sara; Pourhoseingholi, Mohmad Amin; Asadzadeh Aghdaei, Hamid; Zali, Mohammad Reza (Journal of gastrointestinal cancer, 2020)
Purpose To evaluate the prognostic role of BRAF and KRAS mutations after adjustment for microsatellite instability (MSI) in Iranian colorectal cancer (CRC) patients. Methods BRAF and KRAS mutations and MSI status were assessed in 258 Iranian subjects with CRC. Two hundred fifty-eight consecutive stages I-IV CRC patients, who underwent surgical resection of adenocarcinoma from 2012 to 2016, were enrolled in the research. Pyrosequencing and Cast-PCR methods were used to the detection of KRAS and BRAF mutations. Kaplan-Meier and Cox regression were employed to estimate hazard ratios (HR) for the association between BRAF and KRAS mutation and overall survival (OS). Results KRAS and BRAF mutations were detected in 36 (14%) and 15 (5.8%) cases of 258 patients with CRC, respectively. BRAF mutations that all comprised V600E and KRAS mutations was found in codon 12 and 13 (80.6% and 19.4%), respectively. KRAS mutations were detected in 19 (15.4%) patients of 123 microsatellite stable (MSS) CRC and it is significantly associated with tumor location and metastasis. BRAF and KRAS mutant vs. wild type of BRAF and KRAS, 5-year OS was 73.3% vs. 82.3% and 83.3% vs. 81.5% (long-rank P > 0.05), respectively. KRAS mutant vs. KRAS-wild-type tumors in MSS/MSI-L status CRC patients, 5-year OS was 78.9% vs. 90.4% (long-rank p = 0.046). Conclusion The present study revealed that BRAF and KRAS mutations were not related to the worse overall survival, while KRAS mutation can be a prognostic factor for overall survival in sporadic microsatellite-stable (MSS) status in Iranian CRC patients.